Enhancing hierarchical factor (HF) and catalytic performance of Bayah’s natural zeolite catalyst for hydrocracking of palm oil to biofuels - Istadi Istadi; Wais Alqurni; Teguh Riyanto (International Journal of Renewable Energy Development, 2026)
This study investigates enhancement of Bayah’s Natural Zeolite (BNZ), an abundant resource from Banten, Indonesia, as a catalyst for hydrocracking palm oil into biofuels. The primary objective was to improve the zeolite's Hierarchical Factor (HF) and overall catalytic performance through a targeted modification process. The modification involved a two-step procedure: a desilication treatment using various concentrations of sodium hydroxide (NaOH) to create mesoporosity, followed by activation with an ammonium acetate (CH₃COONH₄) solution. The structural, textural, and chemical properties of the modified catalysts were systematically characterized using X-ray Diffraction (XRD), X-ray Fluorescence (XRF), and Brunauer-Emmett-Teller/Barrett-Joyner-Halenda (BET-BJH) analysis. The characterization results revealed that the NaOH treatment increased the HF, average pore diameter, pore volume, and specific surface area compared to the untreated BNZ. Catalytic performance was evaluated in a continuous hydrocracking reactor using palm oil as feedstock. Among the modified samples, the BNZ-3 catalyst exhibited the most promising activity, demonstrating an optimal average pore diameter of 3.83 nm and an HF value of 0.069. This catalyst achieved an impressive Organic Liquid Product (OLP) yield of 85.67% and a palm oil conversion rate of 97.22%. The conversion of triglycerides was monitored via Fourier Transform Infrared Spectroscopy (FT-IR) by observing the disappearance of the ester bond absorption peak at 1745 cm⁻¹. Furthermore, Gas Chromatography-Mass Spectrometry (GC-MS) analysis of the distilled biofuel confirmed the presence of desired hydrocarbons fractions, including gasoline, kerosene, and diesel components, alongside minor quantities of alcohols, esters, and acids. The DSC results corroborate the TG and DTG analyses, reinforcing the conclusion that BNZ‑3 experiences more extensive coke deposition and undergoes more intense thermal decomposition than the blank catalyst. These findings underscore the potential of modified natural zeolites as effective, low-cost catalysts for sustainable biofuel production.